Designing an automated matching model to enhance recruitment process - Idwan, Sahar; Fayyoumi, Ebaa; Hijazi, Haneen; Matar, Izzeddin (Institute of Advanced Engineering and Science, 2025)
Detecting qualified candidates for a vacant position is a difficult task, especially when there are numerous applicants. This delays team development in finding the appropriate individual at the right moment. Adopting a well-structured selection process will create opportunities for new aspects and ideas. In this paper, the matching job applicant (MJA) model is developed to assist all parties, the employers and the employees simultaneously by providing a fair, transparent unbiased solution constructed by using a mathematical machine. This provides a clear justification in the decision-making process in addition to advising the applicants with the most suitable positions that fits their qualifications.